Nilai-Nilai Perjuangan Pendidikan Karakter Islam K.H. Abdullah Sa’id - Hilalludin Hilalludin; Adi Haironi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The concept of Islamic education according to K.H. Abdullah Sa'id aims to shape individuals according to the vision of his creation as abid and caliph of Allah. He emphasized two main steps: developing a philosophical view of "human identity" and building an epistemology based on the Koran and Sunnah. This education uses the systematics of revelation, with the stages of the revelation of the Koran as a foundation, to form a vision of an educational movement aimed at building Islamic civilization. The process of character formation is carried out through habituation, attention and example. The Islamic values implemented are reflected in the "Gunung Tembak Charter" which is a guideline for Hidayatullah cadres. This education not only produces graduates, but also individuals who make real contributions to society.